Reorientasi Pemikiran Penggunaan Hukum Pidana Sebagai Sarana Penanggulanagan kejahatan - Lalu Parman (Jatiswara, 2012)
The purposes of this resesearh is to know and ro analyse the role or criminal law in overcome of crimes by using coceptual approach. Crime is a social fenomanon that always exist and develop in accordance with the social development. The use of criminal law as one of tool in overcoming crimes has a stretategic role, however, its paradigm is unpartial again, namely, crime is not seen as the criminal law system separated from the social system only but it must be seen as integratedly that is not separated and to be a union with the social system in achieving social purpose nameloy the social welfare and security. The effectiveness use of the criminal justice system as one of the tool of criminal overcome, mainly from the social purpose aspect namely to achieve social welfare and social defence, must be done by comprehensive and integrated approachs by using conscience since the creation of its legal substance, the legal enforcement process (structue of law) supported by the high cultural law.